PENERAPAN METODE EVERYONE IS A TEACHER HERE UNTUK MENINGKATKAN KEAKTIFAN BELAJAR PESERTA DIDIK KELAS V DI SD MUHAMMADIYAH 2 PONTIANAK - Amalia, Nanda Erka; setyaningrum, saumi; Yusdiana, Yusdiana (Jurnal Karya Ilmiah Pendidik dan Praktisi SD&MI (JKIPP), 2023)
The background of this study is not enough active students to ask and listening when learning currently going on . The purpose of this study is for Describe how students activeness in learning thematic theme 2 before applied the everyone is a teacher here method in class V SD Muhammadiyah 2 Pontianak, Describe how application the everyone is a teacher here method for increase student activeness in learning thematic theme 2 in class V SD Muhammadiyah 2 Pontianak. Describe How active students in learning thematic theme 2 after applied the everyone is a teacher here method in class V SD Muhammadiyah 2 Pontianak. Research this use type study action class (PTK) with use approach quantitative. Based on observations made _ so could concluded : (1) Activeness study participant educate before applied method everyone is a teacher here obtain percentage classification which is 19.35%. including to in classification no active . (2) Application method everyone is a teacher here on study this conducted as much two cycle , two cycle the all conducted by researcher with results implementation study of 95.4 % of _ observed aspects . _ (3) Liveliness study participant educate after applied method everyone is a teacher here obtain classification of 87.09% which is included to in category classification very active . (4) Application method everyone is a teacher here increase liveliness study participant educate from 19.35% to 87.09%.